A titerature review of hydrogen internal combustion engine - Lindqvist, Hjalmar; Overby, Petter (My University, 2024)
This thesis reviews the current challenges of the hydrogen internal combustion engine through a literature study conducted for two main reasons. Firstly to provide an overview of the operation of a hydrogen internal combustion engine and secondly, to gather test data from previous research as well as the researchers’ conclusions. From the literature review, it was presented that hydrogen as a combustion fuel still poses challenges surrounding combustion stability, power density and NOX emissions. Abnormal combustion such as pre-ignition and knock occur often at air-to fuel ratios close to the stoichiometric ratio (34.2:1) causing operation around ϕ = 0.5 − 0.6 to be more optimal. With knock-suppressing methods such as water injection or exhaust gas recirculation, a lean air-to fuel mixture is required to extract maximum possible power while maintaining stable combustion at all engine loads. In the results the test data from all studies were compared and evaluated. Re searchers do not seem to agree on whether port fuel or direct injection is most desirable. Using the different injection systems will therefore come with differing issues to solve. While similar thermal efficiencies to gasoline engines have been achieved in the past 15 years power is still lacking. The highest BMEP achieved by a study (1.215MPa) is around half that of a conventional turbocharged gasoline engine in a passenger vehicle. The studies focusing on performance have been conducted at low engine speeds with low displacement engines providing little data above 2200 RPM showing concern whether a hydrogen combustion engine will have the same characteristics when upscaled and needing more air. Researchers focused on engine performance also lack data regarding NOX occurrence at different operating points but benefit from the consensus between studies to utilize lean air-to-fuel ratios. However, as of today, producing one ton of hydrogen emits five times the amount of CO2 meaning that until hydrogen production can be done with zero emissions the engine concept can not be considered emission-free. Whilst the research has proven that it is possible to construct and operate a hydrogen internal combustion engine there are still areas which need to be improved upon for the engine to function smoothly in a vehicle. Tests need to be done on larger scale engines where factors such as air supply and engine speed can be tested on the road.
Keywords: Internal combustion engine; hydrogen combustion; zero emissions; knock; pre-ignition